Izkazana raven bralne pismenosti in šolski uspeh - Doupona Horvat, Marjeta (Šolsko polje, 2006)
As found also in PIRLS 2001, reading achievement and family income are strongly related. School performance is strongly related to family income as well. Higher family income implies both, higher reading achievement and betterschool performance (measured via grades for Slovene Language and grades for general performance). However, there are exceptions to this rule: childrenwith good grades and low reading achievement are in one group and children with low grades and high reading achievement in the second one. In this paper the two groups are discussed. The analysis showed that the two groups have distinct characteristics regarding family income, parents' education, self-perception etc.
Keywords: branje; bralna pismenost; mednarodne raziskave; učni uspeh; šolske ocene; ocenjevanje; preverjanje znanja